The Prognostic Value of the Developmental Gene FZD6 in Young Saudi Breast Cancer Patients: A Biomarkers Discovery and Cancer Inducers OncoScreen Approach - Assidi, Mourad; Buhmeida, Abdelbaset; Al-Zahrani, Maryam H.; Al-Maghrabi, Jaudah; Rasool, Mahmood; Naseer, Muhammad I.; Alkhatabi, Heba; Alrefaei, Abdulmajeed F.; Zari, Ali; Elkhatib, Razan; Abuzenadah, Adel; Pushparaj, Peter N.; et al. (Frontiers in Molecular Biosciences, 2022)
Wnt signalling receptors, Frizzleds (FZDs), play a pivotal role in many cellular events during embryonic development and cancer. Female breast cancer (BC) is currently the worldwide leading incident cancer type and the cause of 1 in 6 deaths due to cancer disease. FZD receptors expression in cancer was shown to be associated with tumour development and patient’s outcomes including recurrence and survival. FZD6 received little attention for its role in BC and hence we analysed its expression pattern in Saudi BC cohort to assess its prognostic potential and unravel the impacted signalling pathway. Paraffin blocks from approximately 405 randomly selected BC patients aged between 25-70 years old were processed for tissue microarray using automated tissue arrayer and then subjected to FZD6 immunohistochemistry staining using Ventana platform. Besides, Ingenuity Pathway Analysis (IPA) knowledgebase was used to decipher the upstream and downstream regulators of FZD6 in BC. TargetScan and miRabel target-prediction databases were used to identify the potential microRNA to regulate FZD6 expression in BC. Results showed that 60% of the BC samples had low expression pattern while 40% showed higher expression level. FZD6 expression analysis showed a significant correlation with tumour invasion (p<0.05), and borderline significance with tumour grade (p=0.07). FZD6 expression showed highly significant association with the BC patients’ survival outcomes. This mainly due to the overall patients’ cohort where tumours with FZD6 elevated expression showed higher recurrence rates (DFS, p<0.0001, log rank) and lived shorter (DSS, p<0.02, log rank). Interestingly, FZD6 prognostic value was more potent in younger BC patients as compared to late onset of the disease. TargetScan microRNA target-prediction analysis and validated by miRabel showed that FZD6 is a potential target for a considerable number of microRNAs expressed in BC. The current study demonstrates a potential prognostic role of FZD6 expression in young BC female patients and provides a better understanding of the involved molecular silencing machinery of the Wnt/FZD6 signaling. Our results should provide better understanding of FZD6 role in BC and add some knowledge towards paving the path towards precision BC prevention and theranostics.